2003
DOI: 10.1364/josaa.20.001958
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of microstructured optical fibers for wideband dispersion compensation

Abstract: Microstructured optical fibers (MOFs) with small hole-to-hole spacing and large airholes are designed to compensate the anomalous dispersion and the dispersion slope of single-mode fibers. The geometrical parameters that characterize triangular MOFs are chosen to optimize the fiber length and the compensation over a wide wavelength range. A proper design of the photonic crystal fiber geometry allows us to achieve dispersion values of approximately -1700 ps nm(-1) km(-1) at 1550 nm and to compensate the dispers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(27 citation statements)
references
References 17 publications
0
25
0
2
Order By: Relevance
“…As the air-hole diameter is increased, the influence of waveguide dispersion becomes stronger. We can see that it is possible to shift the zero dispersion wavelength to visible to near-infrared (IR) regions by appropriately changing the geometrical parameters such as hole pitch and hole diameter [73], [74] and that a PCF with a very small hole pitch and a large air-hole diameter has large normal dispersion in the 1.55-µm wavelength range [48]. In addition, Fig.…”
Section: Chromatic Dispersion Tailoringmentioning
confidence: 92%
“…As the air-hole diameter is increased, the influence of waveguide dispersion becomes stronger. We can see that it is possible to shift the zero dispersion wavelength to visible to near-infrared (IR) regions by appropriately changing the geometrical parameters such as hole pitch and hole diameter [73], [74] and that a PCF with a very small hole pitch and a large air-hole diameter has large normal dispersion in the 1.55-µm wavelength range [48]. In addition, Fig.…”
Section: Chromatic Dispersion Tailoringmentioning
confidence: 92%
“…It may become possible to design highly different optical signal processing components by combining RE-doped and PCF technology. This may be done using either the high anomalous dispersion in PCFs [27] or the normal dispersion predicted in dispersion compensating microstructured fibers [28].…”
Section: Amplifiers With Novel Dispersion Propertiesmentioning
confidence: 99%
“…It was already demonstrated that PCFs can be used in numerous applications, including chromatic dispersion compensation [2] and supercontinuum generation [3], and to improve the efficiency of fiber lasers [4]. The polarization properties of PCFs are also of particular interest.…”
Section: Introductionmentioning
confidence: 99%